2020
DOI: 10.37605/pjhssr.3.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Nexus Between Consumer Welfare and Marshalian’s Demand Function; Evidence From Pakistan

Abstract: Consumer welfare and their satisfaction is the primary and basic objective of any government, policy makers and economists. The theory of economics encircles from welfares of the consumers. In this regard, the demand function has persuasive role in determining the welfare through purchasing power. That’s why, the consumer welfare is measured from Marshallian’s demand through Indirect Utility Function during 1980-2017 for Pakistan. The variables are stationary at level and in analytical technique, the NLS and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…This could serve as a way to buttress Ebaidalla and Edriess (2015), who found that the macroeconomic environment plays an important role in facilitating remittance inflow into an economy. Further justification is that remittances have been found to be inflationary since they fuel higher consumer spending (Iqbal et al 2013;Rivera and Tullao 2020). However, there is no cause for alarm on the potential endogeneity bias that could ensue as a result of combining remittance and inflation as multiple regressors, given that the two techniques of analysis employed provide for this eventuality.…”
Section: Resultsmentioning
confidence: 99%
“…This could serve as a way to buttress Ebaidalla and Edriess (2015), who found that the macroeconomic environment plays an important role in facilitating remittance inflow into an economy. Further justification is that remittances have been found to be inflationary since they fuel higher consumer spending (Iqbal et al 2013;Rivera and Tullao 2020). However, there is no cause for alarm on the potential endogeneity bias that could ensue as a result of combining remittance and inflation as multiple regressors, given that the two techniques of analysis employed provide for this eventuality.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Nisar and Tufail (2013) examined the remittance-inflation nexus in Pakistan and found that remittances, money supply, and real per capita GDP have a positive impact on inflation in Pakistan. On a similar note, the study by Iqbal et al (2013) also concluded that remittances have fueled inflation in Pakistan. A study by Roy and Rahman (2014), using a vector error correction model, found that remittance has put inflationary pressure on Bangladesh, especially food inflation.…”
Section: Literature Reviewmentioning
confidence: 88%